2018
DOI: 10.1093/mnras/sty1442
|View full text |Cite
|
Sign up to set email alerts
|

Stellar models with calibrated convection and temperature stratification from 3D hydrodynamics simulations

Abstract: Stellar evolution codes play a major role in present-day astrophysics, yet they share common simplifications related to the outer layers of stars. We seek to improve on this by the use of results from realistic and highly detailed 3D hydrodynamics simulations of stellar convection. We implement a temperature stratification extracted directly from the 3D simulations into two stellar evolution codes to replace the simplified atmosphere normally used. Our implementation also contains a non-constant mixing-length … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 58 publications
(80 reference statements)
2
47
0
Order By: Relevance
“…3.4.4. Mosumgaard et al (2018) also found that a T eff shift from a solar-α track with the Eddington T (τ) to a varying-α track with the 3D T (τ) relation (Trampedach et al 2013) is not substantial, ∼ +30 K at log g = 3.2 for 1M ⊙ . We find it similar to the T eff shift from our solar-α to varying-α track for MLT, which is ∼ +24 K at the same log g. This similarity also can be explained by the closeness between Trampedach et al (2014b)'s α values and our 3D-calibrated α values for MLT(BV) with the Eddington T (τ).…”
Section: Stellar Evolution With Varying α Based On the 3d Calibrationmentioning
confidence: 97%
“…3.4.4. Mosumgaard et al (2018) also found that a T eff shift from a solar-α track with the Eddington T (τ) to a varying-α track with the 3D T (τ) relation (Trampedach et al 2013) is not substantial, ∼ +30 K at log g = 3.2 for 1M ⊙ . We find it similar to the T eff shift from our solar-α to varying-α track for MLT, which is ∼ +24 K at the same log g. This similarity also can be explained by the closeness between Trampedach et al (2014b)'s α values and our 3D-calibrated α values for MLT(BV) with the Eddington T (τ).…”
Section: Stellar Evolution With Varying α Based On the 3d Calibrationmentioning
confidence: 97%
“…In this procedure -which also relies on interpolation in T eff and log gthe outer boundary conditions are supplied by T(τ) relations extracted from the 3D simulations by Trampedach et al (2014a), and the models include a variable 3D-calibrated α MLT from Trampedach et al (2014b). This specific solar model is taken from Mosumgaard et al (2018) and is denoted RT2014 in the following.…”
Section: The Trampedach Gridmentioning
confidence: 99%
“…How stellar evolution is affected by employing this parametrisation was initially investigated by Salaris & Cassisi (2015) and Mosumgaard et al (2017). Recently, Mosumgaard et al (2018) published details on how to implement the results in a stellar evolution code, and presented an in-depth analysis of the structural and asteroseismic impact, which turns out to be quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…⋆ E-mail: hg@phys.au.dk (GH) Moreover, with the recent success of three-dimensional (3D) hydrodynamical simulations of outer stellar layers (e.g., Trampedach et al 2013;Magic et al 2013;Ludwig & Steffen 2016;Kupka et al 2018), it is now possible to use averaged simulation results for calibrating convection parameters of 1D stellar models (e.g. Ludwig et al 1999;Trampedach et al 2014b;Magic et al 2015;Houdek 2017;Aarslev et al 2018) or replacing the outer layers of 1D stellar models by averaged 3D simulations for seismic analysis (e.g., Rosenthal et al 1995Rosenthal et al , 1999Piau et al 2014;Sonoi et al 2015Sonoi et al , 2017Magic & Weiss 2016;Ball et al 2016;Houdek et al 2017;Trampedach et al 2017;Jørgensen et al 2018;Mosumgaard et al 2018).…”
Section: Introductionmentioning
confidence: 99%